Performing Animals : History, Agency, Theater - Mattfeld, Monica, 1982-; Raber, Karen, 1961- (Book collections on Project MUSE., 2017)
"A collection of essays that explore the role of performing animals in literature, theater, art, and other media prior to the twentieth century, and discuss recent theoretical work in animal studies, materialism, and post humanism"--Provided by publisher